EFFECT OF BOILING AND MICROWAVE ASSISTED PROCESSING ON THE ANTIMICROBIAL EFFICACY OF VITAMIN–C IN EMBLICA OFFICINALIS - SUTRADHAR, PAYEL; GHOSH, SHALINI; ROY, BINITA KUMARI (International Journal of Current Pharmaceutical Research, 2020)
Objective: The present work aimed to expand the awareness of restoring vitamin-C in its active form on different heat exposures. The effect of microwave-assisted processing and boiling of the aqueous crude extract of citrus fruit Emblica officinalis (amla) has been correlated with its antimicrobial efficacy against E. coli. Methods: The aqueous crude extract of dried amla pulp exposed to microwave radiation(600W,5 min) and boiling (5 min) were titrimetrically estimated for vitamin-C content by DCPIP-(2,6, Dinitrophenol indophenol) method and compared the same with the untreated sample. These three samples were studied for their effect on the growth pattern of E. coli turbidimetrically. The antimicrobial susceptibility test by agar cup well diffusion method was further followed to measure the zone of inhibitions (ZOI) for these three test extracts against E. coli. Results: The total estimated vitamin-C content was 26.76 mg/100g, 25.35 mg/100g and 21.12 mg/100g in the untreated extract (UTE), microwaved extract (MWE) and boiled extract (BE) respectively. At a higher concentration (0.8 mg/ml), the UTE showed a greater ZOI of 20 mm and a comparable ZOI of 18 mm for the MWE against E. coli. In addition, a reduced ZOI of 10 mm was recorded in case of the BE. At a lowest concentration (0.05 mg/ml), the UTE inhibited the growth with a least ZOI of 7 mm, whereas no inhibition zones were detected for MWE and BE at this concentration. Conclusion: The present investigation demonstrated the effect of boiling and microwave-assisted processing on the content of bioactive vitamin-C and its antimicrobial activity. The DCPIP method calculated a more vitamin-C retention in the MWE than the BE. As the boiling method destroyed the vitamin more rapidly, a higher growth rate of E. coli was measured in the presence of BE than the UTE and MWE. In addition, the antimicrobial assay also showed a least inhibitory effect against E. coli in the presence of the BE. A moderate inhibitory effect for MWE was also detected. Thus the present investigation proved that the boiling process destroys vitamin-C present in a food sample to a higher extent than the microwave-assisted processing.